Pengaruh Layanan ATM Setor Tunai Dan M-Banking Terhadap Kepuasan Nasabah Pada Bank Mandiri Bogor - Senny Wirantie; Filani Zikri Hassan; Wimpi Srihandoko (Jurnal Informatika Kesatuan, 2022)
The purpose of this study was to study the effect of cash deposit and M-banking ATM services on credit satisfaction at Bank Mandiri Bogor. Some previous studies conducted with different periods, samples, and methods with various results need further research. In addition, researchers also have an interest in conducting further research because in an increasingly evolving era it has made products in the banking sector easier to use and provide improvements for profit. This study consists of two variables, namely independent taken from service products, namely nominal atm deposit and m-banking, and one dependent variable, commercial satisfaction. Primary data were collected using a questionnaire from 100 respondents who constituted income at Bank Mandiri Bogor. Initially, researchers used validity and reliability tests for the questionnaire. Next, the researcher discusses the classics using multiple linear regression with an error margin of 5%. Finally, the researcher assessed the hypothesis using the T-test, the F-test and the coefficient of determination. The results show that 2 independent variables simultaneously have a significant effect on the dependent variable, 71.1%. Keywords: Service, Atm Deposit Tunia, M-Banking, Customer Satisfaction.